A Toolbox for Rapid Quantitative Assessment of Chronological Lifespan and Survival in Saccharomyces cerevisiae. (1st April 2016) - Chadwick, Sarah R.; Pananos, Athanasios D.; Di Gregorio, Sonja E.; Park, Anna E.; Etedali‐Zadeh, Parnian; Duennwald, Martin L.; Lajoie, Patrick
Abstract : The yeast Saccharomyces cerevisiae provides an unmatched genetic platform to study the mechanisms underlying the aging process. We present a rapid and efficient quantitative assay to measure chronological aging in yeast through fluorescent labeling of dead cells in multiwell plates. We designed an open‐source software to rapidly quantify yeast survival under various conditions, including chronological aging. We employed our assays to study the role of different heat shock proteins in the extension of yeast chronological lifespan by caloric restriction. Abstract : Saccharomyces cerevisiae is a well‐established model organism to study the mechanisms of longevity. One of the two aging paradigms studied in yeast is termed chronological lifespan (CLS). CLS is defined by the amount of time non‐dividing yeast cells can survive at stationary phase. Here, we propose new approaches that allow rapid and efficient quantification of survival rates in aging yeast cultures using either a fluorescent cell counter or microplate imaging. We have generated a software calledanalysr (An alyticalAl gorithm forY eastS urvivalR ates) that allows automated and highly reproducible analysis of cell survival in aging yeast cultures using fluorescent data. To demonstrate the efficiency of our new experimental tools, we tested the previously characterized ability of caloric restriction to extend lifespan. Interestingly, we found that this process is independent of the expression of three central yeast heat shock proteins (Hsp26, Hsp42, Hsp104). Finally, our new assay is easily adaptable to other types of toxicity studies. Here, we assessed the toxicity of various concentrations of acetic acid, a known contributor of yeast chronological aging. These assays provide researchers with cost‐effective, low‐ and high‐content assays that can serve as an efficient complement to the time‐consuming colony forming unit assay usually used in CLS studies.